Can the development of protective factors help disrupt the foster care-to-prison pipeline? An examination of the association between justice system involvement and the development of youth protective factors. Issue 2 (15th March 2021) - Summersett Williams, Faith; Martinovich, Zoran; Kisiel, Cassandra; Griffin, Gene; Goldenthal, Hayley; Jordan, Neil
ABSTRACT: This study explored whether youth protective factors become more or less developed overtime for 4811 youth involved in child welfare using the Child and Adolescent Need and Strengths (CANS) Assessment. Using child welfare administrative data, analyses investigated if the improvement of youth protective factors while in the child welfare system was associated with reducing the risk of justice system involvement. Study findings demonstrated that youth with improved community life strengths, talents/interests, educational strengths, and spiritual/religious strengths were at a significantly lower risk of becoming justice involved while in child welfare. This speaks to the protective effect that positive self-concept in the form of individual talents or creativity, community resources, educational supports, and spiritual/religious encouragement have on youth development and functioning while in the child welfare system, in addition to the potential role of the child welfare system in helping to develop these specific protective factors.